PENGARUH SISTEM PENGENDALIAN INTERNAL PEMERINTAH DAN PEMAHAMAN STANDAR AKUNTANSI PEMERINTAHAN TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN DENGAN EFEKTIVITAS SiPD SEBAGAI VARIABEL MODERATING PADA PEMERINTAHAN KOTA BINJAI - Ocvianita, Ika; Irfan, Irfan; Hani, Syafrida (UNIVERSITAS DHARMAWANGSA, 2025)
This study aims to examine the impact of the Government Internal Control System (SPIP) and the Understanding of Government Accounting Standards on the Timeliness of Financial Report Submission, with the Effectiveness of the Regional Control Information System (SiPD) acting as a moderating variable in the Government of Binjai City. This research adopts a quantitative associative approach, utilizing path analysis through SmartPLS 4 software. A total of 80 questionnaires were distributed for the study. The findings reveal that SPIP has a positive and significant effect on the timeliness of financial report submission. Additionally, the understanding of Government Accounting Standards also has a positive and significant impact. Moreover, the effectiveness of SiPD plays a moderating role, strengthening the relationship between SPIP and the timeliness of financial report submission, as well as enhancing the effect of understanding Government Accounting Standards on the timeliness of financial reporting.